TERRITORIAL FEATURES OF THE DEVELOPMENT OF DEMOGRAPHIC PROCESSES IN THE FERGANA REGION (Scientific journal of the Fergana State University, 2025)
The article analyzes the demographic processes of Fergana, one of the eastern regions of Uzbekistan, in recent years, and also highlights the territorial features of the region. A detailed description of the natural-geographical and socio-geographical living conditions of the region's population, influencing demographic processes, is given. The article draws appropriate conclusions based on the results obtained.